A review of heat stress in chickens. Part I: Insights into physiology and gut health - Brugaletta, Giorgio; Teyssier, Jean-Rémi; Rochell, Samuel J.; Dridi, Sami; Sirri, Federico (Frontiers in Physiology, 2022)
Heat stress (HS) compromises the yield and quality of poultry products and endangers the sustainability of the poultry industry. Despite being homeothermic, chickens, especially fast-growing broiler lines, are particularly sensitive to HS due to the phylogenetic absence of sweat glands, along with the artificial selection-caused increase in metabolic rates and limited development of cardiovascular and respiratory systems. Clinical signs and consequences of HS are multifaceted and include alterations in behavior (e.g., lethargy, decreased feed intake, and panting), metabolism (e.g., catabolic status, fat accumulation, and reduced skeletal muscle accretion), general homeostasis (e.g., alkalosis, hormonal imbalance, immunodeficiency, inflammation, and oxidative stress) and gastrointestinal tract function (e.g., digestive and absorptive disorders, enteritis, paracellular barrier failure, and dysbiosis). Poultry scientists and companies have made great efforts to develop effective solutions to counteract the detrimental effects of HS on health and performance of chickens. Feeding and nutrition have been shown to play a key role in combating HS in chicken husbandry. Nutritional strategies that enhance protein and energy utilization as well as dietary interventions intended to restore intestinal eubiosis are of increasing interest because of the marked effects of HS on feed intake, nutrient metabolism, and gut health. Hence, the present review, divided into Part I and Part II, seeks to synthesize information on the effects of HS on physiology, gut health, and performance of chickens, with emphasis on potential solutions adopted in broiler chicken nutrition to alleviate these effects. Part I provides introductory knowledge on HS physiology to make good use of the nutritional themes covered by Part II.